PENGARUH BERBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa subsp. Chinensis) - Kamelia Dwi Jayanti (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2020)
Pakcoy is a short-lived plant and has the high nutritional content needed by the body. One of the factors that influence the growth and yield of pakcoy is the growing medium. This study aims to determine the effect of various growing mediums on the growth and yield of pakcoy. This study used a randomized block design (4 x 4) with the treatment of M1 (soil), M2 (soil + manure), M3 (soil + sand) and M4 (soil + sand + manure). The results showed that the growing medium is a mixture of soil, sand, and manure gave the highest average value for all observed parameters, although it was not significantly different from the mixed growing medium of soil and manure.